Digital Modernization of Ukraine Economic Processes in the Context of European Integration (Economics and region, 2021)
The peculiarities of the digital economy and its connection with the so-called on-demand economy were studied in the article. The cardinal transformation of participants' production relations, the result of which is the integration of products and services into a single digital system, was studied. The main segments of the digital economy were analyzed by authors. It was proved that the development of technology and automation has a profound effect on the labor force of any country. Adaptation strategies used by governments around the world to mitigate future societal shocks were studied, namely: stimulating the creation of new types of jobs; legislative slowdown in the spread of technology; unconditional basic income (UBI). The level of digitalization of the Ukrainian economy was studied. The share of some digital services in Ukraine and the European Union was given.
Keywords: development; strategies; digital economy; digitalization; digital technologies; digital services